La participación del público en las sitios web de televisión: Estudio del caso de las Corporaciones de Radiotelevisión Públicas de las Comunidades Autónomas en España //Audience participation in television websites: a case study of the public broadcasting - Ayerdi, Koldobika Meso; Ureta, Ainara Larrondo; Onaindia, Irati Agirreazkuenaga; Zubizarreta, José Larrañaga (Contemporanea, 2011)
The development of Internet and the Web 2.0 have multiplied the possibilities available to the television audience for dialoguing with the medium, beyond the television screen. This is in spite of the fact that interactivity in television is not something new. Participatory forms like electronic mail, chat, SMSs, forums, virtual meetings, surveys, blogs or social networks are acquiring a special relevance. At present, these tools are being preferentially incorporated by televisions and aimed at the younger public, given its special predilection for changes and for the use of new technologies. This communication analyses the incorporation of these new forms on the basis of a case study centred on the public televisions of the autonomous communities in Spain.